The Post-Unitarian ‘Uomo Nuovo’: On the Ironical Treatment of History in Federico De Roberto’s I Viceré and Giuseppe Tomasi di Lampedusa’s Il Gattopardo - Lombardi, Giulia (Spunti e Ricerche, 2021)
The immediate, controversial and continuous success of Giuseppe Tomasi di Lampedusa’s Il Gattopardo (1958) brings to the reader’s attention another novel, which was published about half a century before: Federico De Roberto’s I Viceré (1894). Both novels present explicit analogies, but they also show some differences, which are worth investigating. One of those is the narrative strategy used to convey the common theme of both novels, which is the political change taking place in Sicily at the time of Risorgimento. The article’s emphasis is on how the image of the so-called ‘uomo nuovo’ (a social phenomenon emerging in the new Italian State, on the cusp between an authoritarian monarchy and a liberal state) is observed with irony by both narrators. The narrative perspective in I Viceré emphasizes primarily on the general historical, social, moral and anthropological premises that will lead to the fall of a political system and the rise of a new one. In the case of Il Gattopardo, the narrative perspective observes the progress of the political change and its magnitude. The article argues that the irony of the narrating instances on the precise historical moment of Risorgimento should not be read as mere “anti-historical”, but as revealing instead a direct confrontation with history.